Unmasking Bacillus Calmette–Guérin Immune Reconstitution Inflammatory Syndrome in a Perinatal HIV Transmission—A Case Report - Daniel Ivanov; Dimitar Strashimirov; Rusina Grozdeva; Evgeni Penchev; Elena Georgieva; Nina Yancheva (Tropical Medicine and Infectious Disease, 2025)
Bacillus Calmette–Guérin (BCG)-related immune reconstitution inflammatory syndrome (IRIS) is a recognised complication following antiretroviral therapy (ART) initiation in HIV-infected infants. We report the case of a 19-month-old child with undiagnosed perinatally acquired HIV due to maternal nondisclosure. The child developed ipsilateral axillary lymphadenitis at the BCG vaccination site shortly after starting ART. The clinical features and temporal association with ART supported a diagnosis of BCG-IRIS. The child was successfully managed with conservative pharmacological treatment alone—rifampicin, isoniazid, and macrolide therapy—without surgical incision or corticosteroids. Progressive improvement of the lesion was observed, and complete clinical resolution occurred over the following months, alongside immune recovery. This case underscores the importance of recognising BCG-IRIS, even in settings where HIV diagnosis may be delayed, and supports the feasibility of conservative management in paediatric patients, potentially avoiding surgical intervention in settings of localised disease.